QUERYING CADASTRAL PARCEL DATA DEFINED BY INSPIRE URI MODEL BY USING QR CODE: TURKISH CASE STUDY - Polat, Zeynel Abidin; Alkan, Mehmet (YILDIZ TECHNICAL UNIV, 2016)
Together with the development of modern technology, a new communication media for accessing to the quality information has emerged. In order to access quality information faster and more practically, Web technology has been developed by Tim Berners-Lee. With this technology, Web users are able to access to the information in Web environment by entering web site URI (or URL) addresses, searching and following the related links. URIs with not only Web documents also possible to define the real world concepts. URI technology has been started with the identification of spatial objects from this property and has been investigated in this study can be accessed via the web positional information of the object. For this purpose, the spatial objects (plots) for INSPIRE URI specific to each model are defined by reference to a spatial objects and to access web resources that is associated with this definition URI QR (Quick Response) code technology is used. To flesh out the application on the basis of the plot interrogation practices have been implemented by the General Directorate of Land Registry and Cadastre in Turkey an alternative to QR coded interrogation practices designed plots and compared with the current interrogation practices of the parcel. According to preliminary results of the comparison QR code to enter information for users with questioning parcels making improper interrogation practices in preventing the possibility of questioning is reduced to zero and conducted more practical and faster than the current interrogation practices parcel.
Keywords: INSPIRE URI model; QR code; TKGM; querying parcel; Engineering